A Study of Partial Stroke Testing on FISHER ESD Valve - Zaid Bin Najid, Zaid (Universiti Teknologi Petronas, 2010)
Partial Stroke Testing (PST) is an online testing of Emergency Shutdown Valve (ESDV) to test and exercise the functionality of the ESDV so that when real emergency occur, the ESDV will stroke as per required. The reliability of PST implementation in plant through out the world is still in question. The SKG14 (Instruments) has setup an Improvement Working Group (IWG) PETRONAS Group Technology Solution (GTS) to initiate and clarify about PST and establish a standard procedure on PST.